Therapeutic Dose of Hydroxyurea-Induced Synaptic Abnormalities on the Mouse Spermatocyte - Fan, Xiaobo; Zhu, Yunxia; Wang, Naixin; Zhang, Bing; Zhang, Cui; Wang, Yanan (Frontiers in Physiology, 2021)
Hydroxyurea (HU) is a widely used pharmacologic therapy for sickle cell disease (SCD). However, replication stress caused by HU has been shown to inhibit premeiotic S phase DNA, leading to reproductive toxicity in germ cells. Here, we administered therapeutic doses of HU (25 mg/kg and 50 mg/kg) to male mice to explore whether replication stress by HU affects pachytene spermatocytes and causes abnormalities of homologous chromosomes pairing and recombination during prophase I of meiosis. In comparison with the control group, the proportions of spermatocyte gaps presented significantly different in the 25 mg/kg (P<0.05) and 50 mg/kg HU (P<0.05) experimental groups. Moreover, the proportions of unrepaired double-strand breaks (DSB) observed by γH2AX staining also corresponded to a higher HU dose with a greater number of breaks. Additionally, a reduction in the counts of recombination foci on the autosomal SCs was observed in the pachytene spermatocytes. Our results revealed that HU has some effects on synaptonemal complex (SC) formation and DSB repair that suggests possible problems with fertility. Therefore, this study provides new evidence of the mechanisms underlying HU reproductive toxicity.